2017
DOI: 10.11648/j.ijnrem.20170201.12
|View full text |Cite
|
Sign up to set email alerts
|

Urban Community’s Participation in Conservation of Open Spaces: A Case of Dar es Salaam City

Abstract: Abstract:Open spaces in cities like Dar es Salaam are facing problem of encroachment and conversion. Despite scholars' recommendation on participatory approach in designing and execution of communities' project to increase participation including Conservation of Open Spaces (COSP). The study used questionnaire survey and participatory approach tools to gather information. Results show that majority of the respondents are aware of specific types and functions of existing open spaces in the study area. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…Mostly, the residents perceive built heritage rehabilitation as an expensive act that does not generate economic benefit. This assumption is consistent with the findings of Hassan (2017). This result can be explained by the fact that the built heritage of the old city of Constantine, contrarily to the Maghreb old cities such as Tunis, Marrakech and Fez, is not effectively integrated in a sustainable economic strategy that can improve the properties' land value and generate income for the residents.…”
Section: Built Heritage Rehabilitationsupporting
confidence: 88%
See 1 more Smart Citation
“…Mostly, the residents perceive built heritage rehabilitation as an expensive act that does not generate economic benefit. This assumption is consistent with the findings of Hassan (2017). This result can be explained by the fact that the built heritage of the old city of Constantine, contrarily to the Maghreb old cities such as Tunis, Marrakech and Fez, is not effectively integrated in a sustainable economic strategy that can improve the properties' land value and generate income for the residents.…”
Section: Built Heritage Rehabilitationsupporting
confidence: 88%
“…As is a characteristic of African countries (Hassan, 2017), males outnumbered females as the heads of households in the study sample. Otherwise, the data on education level seem relevant: half of the households' heads have a higher level of education, as revealed by the exhaustive study of URBACO (1985).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the respondents (69.3%) declared to gain benefits from the forest: ecological services, honey, timber, medicines (see Figure 3). These findings are similar to the ones observed by Hassan (2015) who observed that the majority of the local community in Dar es Salaam (Tanzania) thinks that conservation of open spaces is costing, but also beneficent. Several researchers all over the World recognized the ecological benefits of green spaces, demonstrating that urban forests and parks work as a beneficial space for physical and psychological wellbeing (Hartig et al, 2014;van den Berg et al, 2018;Wheeler et al, 2018).…”
Section: Benefits and Problems Deriving From Njiro Forestsupporting
confidence: 90%
“…For instance based on ownership, Roy et al, (2018) categorized green spaces into three types of privately owned and used, open to use by general public and open to use upon payment. On the other hand, based on the nature, Mensah (2014) and Hassan (2015) provided five categorizes of green spaces of semiprivate space, designated greenery, public green areas, public and private tree plantations, rangeland and forests close to urban areas, natural forest under urban influence and trees planted for environmental protection and beautification.…”
Section: Introductionmentioning
confidence: 99%